2007
DOI: 10.1098/rsta.2007.2148
|View full text |Cite
|
Sign up to set email alerts
|

Probing the localized-to-delocalized transition

Abstract: Detailed understanding of the transition between localized and delocalized behaviour in mixed valence compounds has been elusive as evidenced by many interpretations of the Creutz-Taube ion, [(NH 3 ) 5 Ru(pz)Ru(NH 3 ) 5 ] 5C . In a review in 2001, experimental protocols and a systematic model to probe this region were proposed and applied to examples in the literature. The model included: (i) multiple orbital interactions in ligand-bridged transition metal complexes, (ii) inclusion of spin-orbit coupling which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 53 publications
3
48
1
Order By: Relevance
“…The designation of localized oxidation states in this and related mixed-valence intermediates is a convenience. There is evidence for strong electronic coupling across the -oxo bridge, and oxidation states may be delocalized, (O)Ru 4.5 Ru 4.5 (O) 3ϩ (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The designation of localized oxidation states in this and related mixed-valence intermediates is a convenience. There is evidence for strong electronic coupling across the -oxo bridge, and oxidation states may be delocalized, (O)Ru 4.5 Ru 4.5 (O) 3ϩ (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the singly covalently linked tpy À tpy counterpart, the "rigid" tppz backbone is highly conjugated and a much stronger p acceptor that typically yields structures displaying effective bridge-mediated electronic coupling and large extents of charge delocalization across the metal centers. [2][3][4][5] In dyad A, the photosensitizing (Ru P ) and catalytic (Ru C ) components are well defined in that these two modules are connected by a single covalent bond. Although this type of (supra)molecular distinction and denotation of the chromophore-catalyst blocks is less clear in the new tppz-bridged dinuclear system, its {(tpy)RuA C H T U N G T R E N N U N G (tppz)} and {(tppz)Ru-A C H T U N G T R E N N U N G (bpy)(L)} fragments (i.e., all-polypyridyl and chloro/aquo moieties, respectively) will also be termed Ru P and Ru C throughout the text for consistency of language within the comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…It has been thought for some time that the correctness of a completely delocalized description on the vibrational time scale was validated by the smooth variation of intramolecular infrared frequencies as the charge on the ion increases from C4 to C5 and C6 (Beattie et al 1976;Best et al 1989) and by the demonstration that the excited intervalence state had zero dipole moment (Oh et al 1991). However, quite recently, Demadis et al (2001) presented compelling evidence that many mixed-valence ions may be regarded as occupying the class 2-3 borderline and suggested that the Creutz-Taube ion may also be so described (Concepcion et al 2008). The evidence in question is the occurrence of weak symmetric modes in the infrared spectrum (Furholz et al 1984) and weak asymmetric modes in the resonance Raman spectrum (Lu et al 1995).…”
mentioning
confidence: 99%